Thomson Reuters´ new citation indexes offer opportunities to improve university rankings - Robinson-García, Nicolás; Torres-Salinas, Daniel (Anuario ThinkEPI, 2015)
In the last few years, Thomson Reuters has launched two new scientific data sources: Book citation index and Data citation index. The renowned family of citation indexes has been expanded to six members, including journal articles, proceedings papers, books, book chapters and research data. For the first time ever we have the chance to include this wide variety of scientific formats in developing bibliometric tools such as university rankings. For some, this would end the serious coverage limitations derived from their exclusive reliance on journal articles. In this short article we suggest the creation of a ranking of Spanish universities based on the various citation indexes and we reflect on their potential interest as well as on their limitations.
Keywords: University rankings; Thomson Reuters; Databases; Books; Scientific data; Book citation index; Data citation index; Coverage by areas.